Application of Generative Artificial Intelligence (GenAI) to Enhance English Listening Skill for Undergraduate Chinese Student - Chu, Weifang; Khwankaew, Apichaya; Zhao, Shujuan; Ye, Chuanjian; Petsangsri, Sirirat (My University, 2025)
This research aims to develop a GenAI learning activity for English news listening proficiency based on the ADDIE model and to study the effectiveness of the GenAI learning activity on English news listening proficiency for 42 first-year undergraduates of Chuxiong Normal University. This study followed the five steps of the ADDIE model: analysis, design, development, implementation, and evaluation. The data were analyzed using descriptive statistics. The result of the students demonstrating significant improvement in their English listening proficiency, evidenced by the increase in post-test mean scores, was substantial (p < 0.05). Moreover, our learning activity is designed for students to effectively use GenAI to generate pictures, helping them better understand news content and vocabulary in various contexts.
Keywords: GenAI; listening skill; technology enhanced learning